2021
DOI: 10.31235/osf.io/qcmez
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Verbal Aggression on Social Media: How, why and its Automatic Identification

Abstract: In recent times, verbal aggression and related phenomena of hate speech, abusive language, trolling, etc. have become a major problem over social media. In this paper, I present the results of a large-scale quantitative study of aggression based on a target-based typology in a manually-annotated multilingual dataset of over 20,000 Facebook comments and tweets each written in Hindi, English or code-mixed Hindi-English. Taking insights from this study, I develop 2 different classifiers for detecting aggression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 6 publications
(7 reference statements)
0
10
0
Order By: Relevance
“…From a current observation, there are some works of detecting hate speech vs. vulgarity in Kumar et al (2018b), which leads to the scope to differentiate speech vs. vulgarity into covert and overt aggression. Dinakar et al (2011) had completed the work relating to cyber-bullying.…”
Section: Text-based Sentiment Analysismentioning
confidence: 96%
See 2 more Smart Citations
“…From a current observation, there are some works of detecting hate speech vs. vulgarity in Kumar et al (2018b), which leads to the scope to differentiate speech vs. vulgarity into covert and overt aggression. Dinakar et al (2011) had completed the work relating to cyber-bullying.…”
Section: Text-based Sentiment Analysismentioning
confidence: 96%
“…The online platform is not considered just a matter of nuisance but has been marked as a significant criminal activity that can be dangerous for many people (Kumar et al 2018b). So, it is essential to take some preventive action to provide a safeguard to the people of the web.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the models can capture the true meaning of the sentence very well; some are good at less computation process. R. kumar et al showed an LSTM model for detecting aggressive comments on social media [1]. They used the combined data of both Trac-1 and Trac-2 workshops.…”
Section: Related Workmentioning
confidence: 99%
“…At the point when we incorporate the messages posted by bots and phony records, disdain discourse turns out to be too normal to ever be distinguished and directed physically. [7] Meanings of online disdain: Instead of one single common meaning, the writing is contained with numerous definitions with particular ways to deal with online disdain. https://doi.org/10.1051/itmconf/20224403034 ICACC-2022 Table 1: Definition of Online Hate [8] The issue of distinguishing disdain discourse has been tended to by different analysts in various ways.…”
Section: Literature Surveymentioning
confidence: 99%